Batteries: A 3D Hybrid of Chemically Coupled Nickel Sulfide and Hollow Carbon Spheres for High Performance Lithium–Sulfur Batteries (Adv. Funct. Mater. 33/2017). (4th September 2017) - Ye, Chao; Zhang, Lei; Guo, Chunxian; Li, Dongdong; Vasileff, Anthony; Wang, Haihui; Qiao, Shi‐Zhang
Abstract : In article number1702524, Haihui Wang, Shi‐Zhang Qiao, and co‐workers report a novel 3D hybrid sulfur host of nickel sulfide (NiS) and carbon hollow spheres for lithium‐sulfur batteries. The novel sulfur host, produced by a new synthetic method, possesses a unique hollow structure with nanosized NiS uniformly distributed on the carbon spheres, contributing to its high performance.